Health Regulatory Focus, Selection Optimization and Compensation Strategy and Sports Practice: A Mediational Analysis. (22nd April 2019) - Laroche, Manon; Roussel, Peggy; Mascret, Nicolas; Cury, François
Abstract: This study aimed to investigate associations of health promotion and prevention regulatory foci with sports practice, and examined the Selection, Optimization and Compensation (SOC) process behind the positive relationship between health promotion focus and sports practice. A cross-sectional study was conducted with 513 French volunteer sports participants aged from 18 to 82. Participants completed an online self-report survey measuring health regulatory foci, SOC strategy, Amount of Sports Practice (ASP), health condition, and educational level. Path analysis main results (χ 2 = 16.64; df = 5; p < .01; RMSEA = 0.067; CFI = 0.98; R 2 = .24) demonstrated that ASP was positively related with health promotion focus (β = .13, p < .01), SOC strategy (β = .28, p < .001) and negatively related with health prevention focus (β = –.20, p < .001). SOC strategy was positively related with health promotion focus (β = .39, p < .001) and bootstrapping analyses revealed that this strategy partially mediated the positive relationship between health promotion focus and ASP, 95% CI [.13, .29]. Finally, additional analyses showed that it was specifically the elective selection, optimization and compensation sub-components of SOC strategy which played mediating roles in this link, [.13, .29] < 95% CI < [.13, .29]. For the first time in the literature, these results evidenced direct links between health regulatory foci and sports practice, and a mechanistic pathway between health promotion focus and sports practice. The theoretical and applied implications of these results for sports promotion are discussed.